Rogue State : A Guide to the World's Only Superpower - Blum, William (GHQ,Rawalpindi, Pakistan Army Education Publishing House, 2005)
Blum came by his book title easily: He simply tested America by the same standards we use to judge other countries. The result is a bill of wrongs$1 (Ban especially well-documented encyclopedia of malfeasance, mendacity and mayhem that has been hypocritically carried out in the name of democracy by those whose only true love was power.s
Includes Notes and Index
Keywords: United States -- Diplomatic Relations -- Intervention (International Law) -- Military Policy -- Human Rights--Government Policy